Energy efficient heating and ventilation of large halls - Kabele, Karel; Hojer, Ondřej (REHVA guidebook ;, 2011)
The guidebook is focused on modern methods for design, control and operation of energy efficient heating systems in large spaces and industrial halls. The book deals with thermal comfort, light and dark gas radiant heaters, water radiant strips heating, floor heating and industrial air heating systems. Various heating systems are illus- trated with case studies. Design principles, methods and modeling tools are presented for various systems.